Implementation of the Rehabilitation Program for Uninhabitable Houses - Arif, Ahmad Zaidan; Murodi, Ahmad; Rantau, Muhamad Ibrahim (International Journal of Education, Information Technology, and Others, 2024)
Implementation of uninhabitable housing assistance is a program to improve the lives of the people, especially for the poor. The implementation of the Non-Occupable Housing Program is carried out directly by the Tangerang City Social Service. The Implementation of Non-Occupable Houses Program is inseparable from the successful implementation to be achieved including Communication, Resources, Disposition, and Bureaucratic Structure. The purpose of this study was to determine the Implementation of Uninhabitable Homes Program in Porisgaga Baru Village, Tangerang City and to identify the obstacles to the Implementation of the Unliveable Housing Program in Porisgaga Baru Village Village, Tangerang City. However, the authors suggest that the Tangerang City Social Service be able to collect data and supervise beneficiaries of Unhealthy Houses and collaborate with villagers so that beneficiaries are on target for the poor.